2020
DOI: 10.1016/j.future.2019.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the social evolution of the Java community in Stack Overflow: A 10-year study of developer interactions

Abstract: Today, Social Media is a key information source for a wide range of domains as a means to gain a better understanding of information flows and user communities. This work introduces a methodology combining machine learning and graph mining approaches to address relevant aspects of quality of service and user intrinsic motivation from the user's perspective. The focus of the present analysis is set on the social interactions among software developers via Stack Overflow. Over the last 10 years, software develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The dataset of Stack Exchange, a popular SQA, containing questions and answers posted from August 2008 to December 2016 was used for this work. It contains several XML files related to different attributes of the post (questions and answers) 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dataset of Stack Exchange, a popular SQA, containing questions and answers posted from August 2008 to December 2016 was used for this work. It contains several XML files related to different attributes of the post (questions and answers) 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Social Question Answering sites (SQAs) refer to online platforms that allow Internet users to ask questions on any topic, and obtain answers from others in the community [1][2][3]. These platforms leverage the wisdom of crowds [4], and facilitate prompt information seeking among the masses [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it has been reported that females, who encounter other members of the same gender, are more likely to engage sooner than those who do not in Stack Overflow [32]. Another significant discovery discloses a stronger tendency among women to post more questions, whereas males to yield more answers, resulting in fewer thumb-ups for them, giving raise to lower average reputation scores for females [33]- [35]. Working under these findings, they designed a reputation strategy to lessen the gender gap that rewards points for publishing questions and answers to the same level.…”
Section: B Gender Identification On Cqa Platformsmentioning
confidence: 99%
“…The questions of Q&A communities are generally tagged with program languages such as Java and Python [ 33 ]. These tags partition a Q&A community into different language communities where intra-group interactions are more frequent than inter-group interactions [ 34 ], reflecting the aggregation of users. This structure of the Q&A community enables us to explore more conveniently and accurately the characteristics of the whole Q&A community with its certain language community [ 35 ].…”
Section: Normassmentioning
confidence: 99%